Swimmer's shoulder: Anatomical background, causes and prevention - Gmünder, F. (2001)
About the anatomy of the shoulder joint, predisposing factors, and some preventive measures (improve flexibility by stretching, strengthening exercises, improve posture, swimming technique/stroke mechanics).